Analysis of Factors Affecting Numeracy Literacy of Students in Class VIII of SMP Darus Salam - Isnurani, Isnurani; Sukarya, Mohamad (IJBLE Scientific Publications Community Inc., 2023)
This study aims to determine the ability of numeracy value as well as factors that influence the numeracy value of students in class VIII of Darus Salam Junior High School. Quantitative method is the method used in this research. The number of samples in this study were 54 students from a population of 62 students in class VIII of SMP Darus Salam. Questionnaires and tests given to 54 respondents were used as data collection techniques. The results of the data were analyzed by analysis. The results of this study are (1) The numeracy skills of students in grade VIII of SMP Darus Salam fall into the low category with a total percentage of 61.1%; (2) Factors that can affect the numeracy of students in grade VIII of SMP Darus Salam are (a) intelligence; (b) learning motivation; (c) fatigue; (d) family environment; (e) facilities and infrastructure; and (f) teacher competence; and (3) The factor that is more influential on the numeracy of students in grade VIII of SMP Darus Salam is teacher competence.